Purification and antibacterial properties of a novel bacteriocin against Escherichia coli from Bacillus subtilis isolated from blueberry ferments. (July 2021) - Xiang, Yi-Zhou; Li, Xin-Yue; Zheng, Hai-Long; Chen, Jun-Yuan; Lin, Lian-Bing; Zhang, Qi-Lin
Abstract: The novel bacteriocin JS17 was obtained from Bacillus subtilis JSX-5, isolated from blueberry ( Vaccinium uliginosum ) ferments. JS17 was purified by ÄKTA Purifier, semi-preparative reversed-phase high performance liquid chromatography, and nano liquid chromatography coupled with tandem mass spectrometry, in succession. Its molecular mass was 652.37 Da and its amino acid sequence was identified as L-F-R-A-F. A homology BLAST search confirmed JS17 as a novel bacteriocin. JS17 was found to have an extensive antibacterial activity spectrum against both Gram-positive and Gram-negative bacteria. JS17 showed heat tolerance, and it was highly stable over pH 2–10 and was sensitive to proteinase K and pepsin. This indicates that JS17 exhibits protein properties and has application potential under high temperature and acid-base conditions. The minimum inhibitory concentration and minimum bactericide concentration of JS17 against Escherichia coli were 10.56 μg/mL and 22.03 μg/mL, respectively, which is lower than that of most previously described bacteriocins. Furthermore, scanning electron microscopy showed that JS17 bactericidally destroyed the cell membrane integrity of E. coli, resulting in cell dissolution and impaired membrane permeability. This study first purified B. subtilis bacteriocin from fruit ferments, suggesting the potential for using JS17 as a food bio-preservative. Highlights: Bacteriocin-producing Bacillus subtilis was isolated from blueberry ferments. Bacteriocin JS17, purified by SEC columns of AKTA and RP-HPLC. Molecular weight and amino acid composition were determined. JS17 was effective against gram positive and negative bacteria. JS17 was effective at range of temperature (37–121 °C) and pH (2–10).